Comparison of productivity from three stingless bees: Tetragonula sapiens, T. clypearis and T. biroi managed under same feed sources for meliponiculture (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Erwan, Habiburrohman, Wiryawan IKG, Muhsinin M, Supeno B, Agussalim. 2023. Comparison of productivity from three stingless bees: Tetragonula sapiens, T. clypearis and T. biroi managed under same feed sources for meliponiculture. Biodiversitas 24: 2988-2994. The productivity of stingless bee species is affected by the workers' population, especially the foragers' number, queen bee productivity, and the availability of plants as the nectar and pollen sources. The recent study aims to evaluate the productivity of three stingless bee species, Tetragonula sapiens (Cockerell, 1911), Tetragonula clypearis (Friese, 1908), and Tetragonula biroi (Friese, 1898), managed under the same feed sources for beekeeping in stingless bee (meliponiculture). Total of fifteen colonies and every five colonies per species of T. sapiens, T. clypearis, and T. biroi, respectively. The results showed that the different species of stingless bees highly affected the exit activities in the morning and afternoon and brood cell number (p